Studi Pola Ruang dan Fungsi Ruang Puri Agung Kerambitan, Kecamatan Kerambitan, Kabupaten Tabanan, Provinsi Bali - Sumantri, I Gusti Ngurah Rai; Sukewijaya, I Made; Astiningsih, Anak Agung Made (Jurnal Arsitektur Lansekap; Vol. 10, No. 2 Oktober 2024, 2024)
Study of Spatial Patterns and Functions Spaces of Puri Agung Kerambitan, Kerambitan District, Tabanan Regency, Bali Province . Puri Agung Kerambitan is located in Kerambitan Village, Kerambitan District, Tabanan Regency, Bali Province. Puri Agung Kerambitan has its own uniqueness and peculiarity because it is different from the spatial patterns and functions of traditional Balinese houses in general. Puri Agung Kerambitan consists of a building unit as well as a residence and government office during the royal period. Along with the many activities of the castle family, tourism and the development of the times, changes have occurred in the castle environment. This study aims to identify spatial patterns and spatial functions, buildings and the functions of Puri Agung Kerambitan buildings as a form of effort to preserve the culture of historic places, namely cultural tourism (cultural tourism) and heritage tourism (tourism to heritage sites or heritage) in the form of participation, search for data and information center creation. The research method used a survey method with data collection techniques of observation, interviews, and literature study. The identification results show that the spatial pattern of Puri Agung Kerambitan is divided into 9 spaces or fixed based on the principle of sanga mandala , besides that there are 3 additional spaces namely saren gong, teba puri, and telajakan puri . Each spaces has a building that has its own characteristics and functions according to the concept of tri hita karana . The results of the research are expected to be a means of education and information about traditional Balinese landscapes as well as historical tourism objects and cultural preservation in the form of a cultural information center so that they can maintain the existence and sustainability of Puri Agung Kerambitan. It is hoped that the government will also play a role in helping promote tourism and funding the preservation of cultural heritage buildings so that Puri Agung Kerambitan becomes a tourist attraction and increases tourist visits to Tabanan Regency.